2015
DOI: 10.1007/s12206-015-0552-9
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer characteristics in a channel fitted with zigzag-cut baffles

Abstract: The heat transfer characteristics were experimentally investigated in a wind channel with different types of cut baffles for heat transfer augmentation. The aim of using zigzag-cut baffles is to create 3D flow structure behind the baffles instead of transverse vortex flow leading to enhance heat transfer. In this study, 4 types of baffles were examined; conventional baffle (Rectangular cross section with no cut), baffle with rectangular zigzag-cut, baffle with triangle zigzag-cut at 45 degree and at 90 degree.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In addition, finned zigzag tube demonstrates an increase of thermal performance by 59% in laminar flow regime compared to a finned straight tube [63]. Also, Nuntadusit et al [64] showed the optimum performance of rectangular zigzag-cut baffle against the rectangular cross-section with no cut and triangle zigzag-cut baffles at Reynolds number of 2×10 4 . The upstream and downstream sides of the baffle promote the efficient transfer of heat because of flow acceleration and low friction factor.…”
Section: Zigzag Tube Design Of the Heat Exchangermentioning
confidence: 99%
“…In addition, finned zigzag tube demonstrates an increase of thermal performance by 59% in laminar flow regime compared to a finned straight tube [63]. Also, Nuntadusit et al [64] showed the optimum performance of rectangular zigzag-cut baffle against the rectangular cross-section with no cut and triangle zigzag-cut baffles at Reynolds number of 2×10 4 . The upstream and downstream sides of the baffle promote the efficient transfer of heat because of flow acceleration and low friction factor.…”
Section: Zigzag Tube Design Of the Heat Exchangermentioning
confidence: 99%
“…4 and Fig. 5 show the velocity distribution along the pipe at the same value of Re =10000 and PR (1,3,5).…”
Section: B Nusselt Numbermentioning
confidence: 99%
“…Fig. 14 shows the contour of the temperature of the smooth pipe and baffled pipe (arrangement 1 and 2) at the same Re=10000 and PR (1,3,5). Fig.…”
Section: Evaluation Of Thermal Performancementioning
confidence: 99%
See 1 more Smart Citation